Group Guidance with Role-Playing Technique based on Tepa Selira Values as an Effort to Increase Tolerance in Secondary School Students: A Systematic Literature Review - Dinda Putri Abadi; Khairul Bariyyah; Henny Indreswari (Journal of Cultural Guidance and Counseling, 2025)
The problem of intolerance is one of the three big sins that are rampant in the world of education. Guidance and counseling are one of the efforts in improving tolerance attitudes in students. The objectives in this study are 1) to identify a group guidance model with role-playing techniques; 2) to identify elements of tepa selira values as an effort to increase tolerance among students as an individual; 3) to construct a group guidance model with role-playing techniques based on tepa selira values to increase tolerance in high school students. The research method employs a systematic literature review, which involves several stages, including collecting literature and discussing the results. So that the results obtained in this study are 1) the production of group guidance models with role-playing techniques; 2) Analysis of the elements of virtue values in tepa selira local wisdom; and 3) the formation of group guidance model construction with role-playing techniques based on tepa selira values to increase student tolerance. It can be concluded that there are role-playing techniques that can be integrated with local wisdom, one of which is the value of tepa selira as a group guidance model to improve students' tolerance.